Fibrinogen: cardiometabolic risk marker in obese or overweight children and adolescents - Waldeneide F. Azevedo; Anajás S.C. Cantalice; Nathalia C. Gonzaga; Mônica O. da S. Simões; Anna Larissa V. Guimarães; Danielle F. de Carvalho; Carla Campos Muniz Medeiros (Elsevier, 2015)
ABSTRACT OBJECTIVES: To determine the prevalence of increased serum fibrinogen levels and its association with cardiometabolic risk factors in overweight or obese children and adolescents. METHODS: Cross-sectional study with 138 children and adolescents (overweight or obese) followed at a reference outpatient clinic of the public health care network. Fibrinogen concentration was divided into quartiles, and values above or equal to the third quartile were considered high. The association between high fibrinogen values and cardiometabolic risk factors was assessed using Pearson's chi-squared test or Fisher's exact test, as necessary. Logistic regression was used to adjust variables predictive of fibrinogen levels. Analyses were performed using SPSS version 22.0 and SAS software, considering a confidence interval of 95%. RESULTS: Serum fibrinogen levels were elevated in 28.3% of individuals, showing association with the presence of high CRP (p = 0.003, PR: 2.41, 95% CI: 1.30-4.46) and the presence of four or more risk factors (p = 0.042; PR: 1.78, 95% CI: 1.00-3.17). After a logistic regression, only elevated CRP remained associated with altered fibrinogen levels (p = 0.024; PR: 1.32; 95% CI: 1.09-5.25). CONCLUSIONS: Increased fibrinogen was prevalent in the study population and was associated with ultrasensitive C-reactive protein and the presence of four or more cardiovascular risk factors; it should be included in the assessment of individuals at risk.